2010
DOI: 10.1002/gps.2481
|View full text |Cite
|
Sign up to set email alerts
|

Relation between frontal lobe symptoms and dementia severity within and across diagnostic dementia categories

Abstract: In FTD patients, frontal lobe symptoms were severe in the mild, moderate and severe dementia stages although the nature of frontal lobe symptoms depended on disease severity. AD and DLB patients displayed more frontal lobe symptoms in the advanced disease stages as compared to disease onset, suggesting gradual frontal lobe involvement as the disease progresses. The nature of frontal lobe symptoms related to dementia severity differed between AD, DLB and FTD patients, suggesting different patterns of frontal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The MFS is a validated clinical and behavioral assessment scale that measures frontal lobe features and reliably discriminates frontotemporal dementia (FTD) from AD patients with a sensitivity and specificity of almost 90% and with good inter-and intra-rater reliability (Aries et al, 2010;De Deyn et al, 2005). According to the instructions for administration and scoring, the MFS was obtained by summating scores in a standardized fashion on 10 items.…”
Section: Bpsd Assessmentmentioning
confidence: 99%
“…The MFS is a validated clinical and behavioral assessment scale that measures frontal lobe features and reliably discriminates frontotemporal dementia (FTD) from AD patients with a sensitivity and specificity of almost 90% and with good inter-and intra-rater reliability (Aries et al, 2010;De Deyn et al, 2005). According to the instructions for administration and scoring, the MFS was obtained by summating scores in a standardized fashion on 10 items.…”
Section: Bpsd Assessmentmentioning
confidence: 99%
“…Furthermore, DLB can present with prominent behavioural symptoms,13 a dysexecutive syndrome14 and primitive reflexes,15 making it difficult at times to distinguish it from FTD clinically.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to AD, DLB has been characterized by a relatively high prevalence of hallucinations, delusions, anxiety, anhedonia, and loss of energy occurring in earlier stages of disease (5) based on the Mini-Mental State Examination (MMSE) (6). The retrospective nature of these findings limited the inferences that could be made; however, similar results were obtained from prospective studies of neuropsychiatric changes in personality traits (7, 8) arising from DLB. On the Blessed Dementia Scale (9) (BDS), caregivers of DLB patients were more likely than AD caregivers to endorse behaviors such as diminished emotional responsiveness, apathy, purposeless hyperactivity, and relinquished hobbies subsumed under a factor of “passivity” despite noting similar levels of irritability and disinhibition (8).…”
Section: Objectivementioning
confidence: 81%
“…A series of studies (7, 10) examined the relationship between DLB and behaviors common to frontal lobe damage. Using a measure previously shown to differentiate frontotemporal dementia from AD [Middelheim Frontality Score (MFS) (11)], investigators found no difference in clinically diagnosed DLB and AD patients in the frequency of frontal lobe behaviors when divided by dementia severity.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation